2011
DOI: 10.1007/s12275-011-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Escherichia coli from neighboring small-scale dairy farms

Abstract: The genetic diversity and population structure of Escherichia coli isolates from small-scale dairy farms were used to assess the ability of E. coli to spread within the farm environment and between neighboring farms. A total of 164 E. coli isolates were obtained from bovine feces, bedding, cow teats and milk from 6 small-scale dairy farms. Ward's clustering grouped the isolates into 54 different random amplified polymorphic DNA (RAPD) types at 95% similarity, regardless of either the sample type or the farm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…However, literature suggesting frequent transmission between farms is rare. This study adds weight to a growing body of evidence, concurring with the results of two North American studies by Wetzel et al [27] and Rosales-Castillo et al [28]. The former found genetically indistinguishable isolates on neighbouring Ohio dairy farms whilst the latter reported the spread of E. coli O157 isolates between Mexican cattle farms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, literature suggesting frequent transmission between farms is rare. This study adds weight to a growing body of evidence, concurring with the results of two North American studies by Wetzel et al [27] and Rosales-Castillo et al [28]. The former found genetically indistinguishable isolates on neighbouring Ohio dairy farms whilst the latter reported the spread of E. coli O157 isolates between Mexican cattle farms.…”
Section: Discussionsupporting
confidence: 90%
“…The farm management questionnaire used in both Survey 1 and 2 did not ask about contacts with other farms so this potential transmission network cannot be tested formally. However, Rosales-Castillo et al [28] identified milking and other staff movement as a risk factor for farm-to-farm transmission. An alternative hypothesis could be that the clustering implies proximity to a shared environmental reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used in the RAPD assays have been successfully used to obtain E. coli fingerprints (34). RAPD assays are robust enough to reveal genetic diversity between ETEC strains in a restricted geographical area (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of E. coli, in the feces of individual or groups of cattle, farm, feedlot, or packing plant environ ments, and cattle in those environments have been characterized by various molecular techniques (19,23,24,27). In general, the findings have been that E. coli populations in cattle and their environments are very diverse.…”
Section: Numbers Of Genotypes Determined By Multiple-locus Variablementioning
confidence: 99%
“…Those strains might be acquired from strains persisting in the plant lairage and/or road trailers or in feedlot cattle throughout the region. The latter possibility must be considered because the same strains of E. coli have been recovered from widely separated farms in some regions (24). Further investigation of this matter would seem to be required.…”
Section: Numbers Of Genotypes Determined By Multiple-locus Variablementioning
confidence: 99%